TREATMENT OF SPORT INJURIES WITH ACUPUNCTURE: A LITERATURE REVIEW - Gentil,Luiza Borges (2018)
ABSTRACT As acupuncture is growing in popularity in Brazil and worldwide, it is necessary to study the benefits and possibilities of this type of treatment more in depth, especially as it is believed to produce fast results with few side effects and does not involve substances banned in sports. Thus, it seems like a good option to be considered as main or adjuvant therapy in sports-related injuries. In order to gain more knowledge about this subject, this article is an integrative review analyzing the publications of the period between January 2012 and January 2017 on the Cochrane and Pubmed platforms that analyzed acupuncture in the treatment of sports injuries. We found 49 articles, 11 of which fulfilled the inclusion criteria: two case reports, three clinical trials and six literature reviews. Although all the articles analyzed produced favorable results with the use of the therapeutic technique in question, flaws in the designs of the studies and the difficulty of creating a placebo control group in acupuncture hinder the qualification of the articles on evidence rating scales. Therefore, it is suggested to the researchers that further studies be published with experimental animal models and observational studies, and that STRICTA recommendations be followed to improve the level of evidence of acupuncture research. Level of Evidence II; Systematic review of level II studies.